Design of a Wireless Multi-Radio-Frequency Channels Inspection System for Bridges - Yan Yu; Jie Wang; Xingquan Mao; Hongbo Liu; Lei Zhou (International Journal of Distributed Sensor Networks)
This paper presents a wireless multi-radio-frequency channels inspection system (WMCIS) based on wireless sensor networks (WSN) for the sake of bridge structural vibration inspection. The designed system consists of a wireless controller and eight wireless nodes with acceleration sensing units. The whole system has 64 collection channels, so every wireless node has eight 24-bit A/D channels. Integrated with acceleration sensing units, an embedded low-power microprocessing unit, a wireless transceiver unit, a large-capacity power unit, and a GPS time synchronization unit, the wireless node has the functions such as data collection, initial analysis, data storage, and wireless data transmission. The wireless controller, equipped with a high-performance computation unit, a wireless transceiver unit, a mobile power source, and an embedded data analysis software, can totally control multiple wireless nodes and receive and analyze data for parameter identification. To verify the performance of the WMCIS, experiments are made on the Caihong Bridge and Jinzhou Bridge in China for inspecting the bridge structural vibration. Experimental results show that the system has the advantages such as fast arrangement, high sampling rate, high resolution, capacity of low-frequency inspection, and GPS clock project for time synchronization and, thus, has good application prospects and practical value.